The Involvement and Resistance of Islamic Defence Action (ABI) at Islamic Student Organization in Pontianak City - Syahbudi, Syahbudi; Fachrurrazi, Fachrurrazi (The Pontianak State Institute of Islamic Studies, 2020)
The phenomena of Islamic Defence Action (ABI) has been raising two argumentations: Firstly, the strengthening of religious conservatism. Secondly, ABI is better organized by conservative group and Muslim middle class such as Muslim student activist. One of the agenda is propagating ABI’s ideas at various regions in Indonesia which used to campaign a slogan “It’s time for Muslims resurgence”, such as in Solo, Aceh, Medan, Yogyakarta, Palembang and other areas. This article argues that ABI at Islamic student activists becomes plasticity as a religious discourse but instability as a common identity to shape a new Islamic social movement agenda in Pontianak. This research focuses on how to understand the forms of engagement and resistance to ABI in context of strengthening pluralism and religious tolerance in Pontianak.